Bright circularly polarized photoluminescence in chiral layered hybrid lead-halide perovskites - Liu, Shangpu; Kepenekian, Mikaël; Bodnar, Stanislav; Feldmann, Sascha; Heindl, Markus W.; Fehn, Natalie; Zerhoch, Jonathan; Shcherbakov, Andrii; Pöthig, Alexander; Li, Yang; Paetzold, Ulrich W.; Kartouzian, Aras; et al. (Science advances, 2023)
Hybrid perovskite semiconductor materials are predicted to lock chirality into place and encode asymmetry into their electronic states, while softness of their crystal lattice accommodates lattice strain to maintain high crystal quality with low defect densities, necessary for high luminescence yields. We report photoluminescence quantum efficiencies as high as 39% and degrees of circularly polarized photoluminescence of up to 52%, at room temperature, in the chiral layered hybrid lead-halide perovskites (R/S/Rac)-3BrMBA2PbI4 [3BrMBA = 1-(3-bromphenyl)-ethylamine]. Using transient chiroptical spectroscopy, we explain the excellent photoluminescence yields from suppression of nonradiative loss channels and high rates of radiative recombination. We further find that photoexcitations show polarization lifetimes that exceed the time scales of radiative decays, which rationalize the high degrees of polarized luminescence. Our findings pave the way toward high-performance solution-processed photonic systems for chiroptical applications and chiral-spintronic logic at room temperature.